(untitled) (Conferencea, 2023)
The present research reviews a programme for improving athletes’ technical and tactical preparation with a consideration of individual combat style. The program has included training models for each style and has considered the characteristics of the current competitive activities of Greco-Roman wrestlers. Thirty qualified Greco-Roman wrestlers of middle-weight categories have participated in the research. Throughout the experiment (a year-long preparation cycle) the indicators of technical and tactical preparedness of the athletes of the experimental group have improved: the efficiency of defence in stand and ground positions has become higher; the reliability and efficiency of attack and defence actions have increased; the wrestlers have begun to perform a greater number of exercises in stand and ground positions, and to perform successful attacks more often; the interval between the attacks has been shortened.